Radiological protection for pregnant women at a large academic medical Cancer Center. (November 2017) - Chu, Bae; Miodownik, Daniel; Williamson, Matthew J.; Gao, Yiming; St. Germain, Jean; Dauer, Lawrence T.
Highlights: Rad safety policies can be effectively applied to declared pregnant medical staff. Max recorded doses were <0.4 mSv in a month and <0.9 mSv over the entire pregnancy. No work modifications were required for >95% of the declared pregnancies. Abstract: Purpose: Most radiation protection programs, regulations and guidance apply specific restrictions to the occupational exposure of pregnant workers. The aim of this study was to compile data from the declared pregnant woman (DPW) radiation protection program over more than 5 years at a large, high-volume, comprehensive oncology academic/medical institution and to evaluate for effectiveness against existing regulations and guidance. Methods: A retrospective review was performed of the data collected as part of the DPW radiation protection program from January 2010 through May 2016, including the number of declared pregnancies, worker category, personal and fetal dosimetry monitoring measurements, workplace modifications, as well as the monthly and total recorded badge results during the entire pregnancy. Results: 245 pregnancies were declared. The mean monthly fetal radiation dosimetry result was 0.009 mSv with a median of 0.005 mSv and a maximum of 0.39 mSv. The mean total dose over the entire pregnancy was estimated to be 0.08 mSv with a median of 0.05 mSv and a maximum of 0.89 mSv. Only 8 (3.2%) of the 245 declared pregnancies required that workplace modifications be implemented for the worker. Conclusions: The implementation of a declared pregnancy and fetal assessment program, careful planning, an understanding of the risks, and minimization of radiation dose by employing appropriate radiation safety measures as needed, can allow medical staff to perform procedures and normal activities without incurring significant risks to the conceptus, or significant interruptions of job activities for most medical workers.